ROLE OF METFORMIN IN CORRECTING HYPERINSULINEMIA, MENSTRUAL IRREGULARITY AND ANOVULATION IN POLYCYSTIC OVARY SYNDROME - Zafar, Shamsa (Journal of Ayub Medical College Abbottabad, 2005)
Background: Previous studies suggest that metformin by reducing hyperinsulinemia is clinically useful in the treatment of polycystic ovary syndrome (PCOS). Our Objective was to observe the role of metformin in correcting oligomenorrhea/amenorrhea and anovulation within six month in hyperinsulinemic women with PCOS. Another aim was to assess the decrease in hyperinsulinemia and body weight by metformin in our population. Methods: This study was carried out at the Department of Obstetrics and Gynaecology, Islamic International Medical Complex (IIMC) Islamabad, from October 2001 to March 2003. Fifty women fulfilling the clinical and biochemical criteria for PCOS and hyperinsulinemia were enrolled. Metformin was started at an oral dose of 500mg/day and maintained at 1500mg for 6 months. Besides ultrasonography and body weight, serum FSH, LH, fasting insulin, fasting blood sugar and creatinine levels were performed. After six months menstrual cyclicity, fasting insulin levels, day 21 serum progesterone and body weights were assessed. Results: After six months of Metformin therapy, menstrual regularity was achieved in 19 out of 22 women (86%). Out of these 11 women (50%) were ovulating at six months. On Metformin, the median fasting serum insulin decreased from 23.6 micro U/ml to 20.2 micro U/ml (P<0.05).There was no significant weight reduction (p=0.096) with Metformin in six months. Data was analyzed using SPSS by paired t-test. Key words; Metformin, PCOS, menstrual irregularity